Painting of blueberries on the south exterior wall of the Yellowknife Inn ... - Campbell, Sandy (University of Alberta Library, 2015)
Blueberries are a common wild fruit that is used as both traditional food and traditional medicine by Indigenous people in Canada's North. This painting is attached to the exterior corrugated metal wall of the Yellowknife Inn, located at the corner of 50th Street and 50th Avenue in Yellowknife, NWT. It is part of a larger exhibit called Urban Art in Yellowknife. ...